The mechanism of sirtuin 2–mediated exacerbation of alpha-synuclein toxicity in models of Parkinson disease - de Oliveira, R.M. (2017)
14834). Received by CS. The funder had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. Fundacao para a Ciencia e Tecnologia https://www.fct.pt/index.phtml.en (grant number SFRH/BPD/41416/2007; SFRH/BPD/64702/2009; SFRH/BPD/109347/2015; SFRH/BD/61495/2009; Ciencia, 2007; SAU-NEU/105215/2008;). Received by RMO, HVM, PG, TFP, TFO. The funder had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. Dorothea Schlozer Program (University of Gottingen). Received by EMS. The funder had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. JPND: Denmark, Innofond; Germany, BMBF; Sweden, SRC; Switzerland, SNSF; United Kingdom, Medical Research Council www.jpnd.eu. Received by TFO. The funder had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. Alexander-von-Humboldt Research Fellowship for Postdoctoral Researchers https.//www.humboldt-foundation.de/web/humboldt-fellowship-postdoc.html. Received by LF. The funder had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. DFG Center for Nanoscale Microscopy and Molecular Physiology of the Brain http://www.cnmpb.de/index.php?lang=en_EN. Received by TFO and MZ. The funder had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. EU Joint Programme - Neurodegenerative Disease Research (JPND) project http://www.neurodegenerationresearch.eu (aSynProtec). Received by TFO. The funder had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.